Long-term exposure to ambient source-specific particulate matter and its components and incidence of cardiovascular events – The Heinz Nixdorf Recall study. (September 2020) - Rodins, Vitalijs; Lucht, Sarah; Ohlwein, Simone; Hennig, Frauke; Soppa, Vanessa; Erbel, Raimund; Jöckel, Karl-Heinz; Weimar, Christian; Hermann, Dirk M.; Schramm, Sara; Moebus, Susanne; Slomiany, Uta; et al.
Highlights: Air pollution from traffic poses higher risk of stroke than from industrial sources. No association found between exposure to air pollution and risk of CHD. Among PM components NH4 and SO4 have higher effect on cardiovascular health. Abstract: Background: Few studies have examined the risk of long-term exposure to source-specific airborne pollutants on incidence of cerebrovascular and cardiovascular events. Objectives: We aimed to estimate the effect of long-term exposure to source-specific air pollution and particulate matter (PM) components on incidence of stroke, coronary heart disease (CHD), and total cardiovascular events (CVE) in the population-based Heinz Nixdorf Recall study (HNR). Methods: We used baseline (2000–2003) and 14-year follow-up data of the HNR Study, an ongoing population-based prospective cohort study in Western Germany. Participants' residential mean exposures to NO2 and total and source-specific PM10, PM2.5, accumulation mode particle number concentration (PNAM ), and PM components were modelled using a dispersion and chemical transport model. We used Cox regression to evaluate the effect of pollutants (per 1 μg/m 3 increase and per interquartile range – IQR) on risk of stroke and CHD, adjusting for socio-demographic characteristics, lifestyle risk factors and nighttime traffic noise exposure. Results: In 4, 105 included participants (aged 45–76 at baseline, 52.5% women), we observed 118 cases of first stroke and 373 cases of first CHD during 46, 748 person-years under risk. The median survival time within the cohort was 13.3 years. No effect of exposure to ambient air pollution on risk of CHD was observed, but distinct effects were observed for stroke. Ambient traffic-specific PM showed a stronger effect on stroke than industry-specific PM: hazard ratios (95% confidence interval) for total, traffic-specific, and industry-specific PM2.5 were 1.16 (1.02–1.34), 2.53 (1.07–5.97), and 1.27 (1.03–1.56) per 1 μg/m 3 increase, respectively. PM components showed no substantially different effects from those of total PM per IQR, but higher associations were observed for NH4 and SO4 per 1 μg/m 3 . However, the exposure contrast of ammonium and sulfate components was very low. Conclusion: Traffic-specific PM exhibited stronger effects than total and industry-specific PM on risk of stroke. Among components, NH4 and SO4 showed higher effects. No effect was observed for PM and CHD.